Enhanced Kerberos Authentication for Distributed Environment Using Two Phases Security - Khalifa, Mahmoud (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
There are many ways to detect , guess ,extract and compute password for online attack, there for using Password protect models are not enough safe to provide the security to the users specially in financial services to restrict unauthorized access to the system like password online guessing attacks which is mainly brute force and dictionary attacks are achieved by limiting the number of attempts made during login [1]. To secure the various systems for the provision of customer services from intrusion common types and specifically Replay attack, Password guessing attack, screen shot, key logger attack we used a model of two phases. First phase used Kerberos model (KDC) as a trusted third party between client and server. So several possible goals accomplished through our study and are summarized as follows: Kerberos uses cryptographic tickets in order to avoid transmitting plain text passwords over the network [2]. To eliminate a number of problems experienced by the Kerberos protocol this is based on the basis of this model. We used RSA encryption to secure the keys session contain username and password concatenated with id code read from external device in order to avoid transmitting plain text which can be detected by key logger attack or screenshot attack . In the second phase we coded all session by apply effectively the CRC algorithm to perform secure communication on an open network, using cryptographic tickets.